Monitoring Dan Evaluasi Dinas Sosial Kota Medan Dalam Penyelenggaraan Kebijakan Program Bantuan Sosial Tunai Kepada Masyarakat Terdampak Covid-19 Di Kelurahan Helvetia Timur - Marisa Ramadhani Ansyah; Siti Hazzah Nur R. (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
Cash Social Assistance is assistance provided by the government to people affected by the Covid-19 pandemic. The problems that occur are the presence of duplicate data in the community, the lack of updating community data, to the lack of effective and efficient services provided. This research aims to describe the monitoring and evaluation of the Medan City Social Service in administering of Cash Social Assistance program policies to people affected by the Covid-19 pandemic in the Eas Helvetia Village. The method used is a descriptive qualitative. Data collection techniques by doing interviews, observations, and document records. Data obtained were analyzed qualitatively by examining all data collected that supported by interviews with the William Dunn (2000) theory approach which suggested that monitoring and evaluation could be seen by compliance, inspection, accounting, and explanation. The result of this research indicate that the monitoring and evaluation is not going well. This can be seen from the determination of the potential recipients has not been in accordance with technical instructions, socialization has not been carried out, between targets and realization are not balanced, and from the results of the evaluation there has been no real action.